2005
DOI: 10.1136/ip.2004.007724
|View full text |Cite
|
Sign up to set email alerts
|

Child and adolescent injury as a result of falls from buildings and structures

Abstract: Objective:To examine incidence, demographic risk factors, and patterns of injury resulting from falls from buildings and structures in areas with and without a legislation based prevention programme.Design and setting:The Health Care Cost and Utilization Project (KID-HCUP) was used to produce national estimates of hospital admissions due to falls from buildings in the US. Areas of New York with and without window guard legislation were identified through the New York Statewide Planning and Research Cooperative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
54
0
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(58 citation statements)
references
References 21 publications
2
54
0
2
Order By: Relevance
“…1,[3][4][5][6]8,9,[11][12][13]16 There was seasonal variation, with more window falls during the spring and summer months. The rate of injury among younger children (0 -4 years of age) was greater than that among older children (5-17 years of age), and younger children were more likely to sustain serious injuries, as demonstrated by their increased risk of hospitalization or death.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…1,[3][4][5][6]8,9,[11][12][13]16 There was seasonal variation, with more window falls during the spring and summer months. The rate of injury among younger children (0 -4 years of age) was greater than that among older children (5-17 years of age), and younger children were more likely to sustain serious injuries, as demonstrated by their increased risk of hospitalization or death.…”
Section: Discussionmentioning
confidence: 99%
“…A national epidemiological study on pediatric falls from buildings and structures, based on a data sample from 27 states, was published in 2005. 9 However, that study was based on hospitalization data, which did not include multiyear trends or details regarding the circumstances of the injury events, which are important for developing prevention strategies.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In response to injury incidence data, the New York City Board of Health passed a law requiring property owners of multiple-story buildings to provide window guards for all dwellings with children under 10 years of age. This effort resulted in a 96% reduction in hospital admissions for falls from windows (99). Window guards are recommended for windows on the first floor over 12 feet high and on all windows above the first story.…”
Section: Window Guard Mandates (Strong Evidence)mentioning
confidence: 99%
“…In our study, the excess of the cases of falling from height was noted. When this subject was examined, it was observed that protective safety precautions for children at doors and windows in environments where children are found were legally mandatory in developed countries (17). We think that this kind of measures should also be taken rapidly in our country and compliance of parents with applications related with window safety will decrease the mortality to a great extent.…”
Section: Discussionmentioning
confidence: 99%